Chilton's Auto repair manual, 1940-1953 : for earlier model American cars. - 4 0 16; Auto repair manual, 1940-1953.; 5 (Radnor, Pa. ; Ontario, Canada : Chilton Book Company ; Thomas Nelson & sons, Ltd., 1971)
Includes information on repair and replacement for American cars massproduced from 1940-1953.
Keywords: 2 -- 0; 6; Maintenance and repair.;Maintenance and repair. -- Automobiles;Automobiles; 20; 2